Involving 13-14 Year-Old Athletes in Athletics - Sharipova Dilyara Djumaniyozovna; Mamanova Aziza Abdukhalik qizi (International Journal on Integrated Education, 2022)
This article presents our theoretical views on how to interest and select students in the athletics section.